Perspectives of Young People with Neuromuscular Diseases Regarding Their Choice of Educational Programs and Possibilities to Complete Program Requirements - Charlotte Handberg; Helle Munkholm; Ann-Lisbeth Højberg (SAGE Publishing, 2024)
Young people with impaired functioning and/or disability do not receive as much education or as high an education as fully functioning young people, thus limiting their job opportunities. Therefore, the aim of this study was to investigate perspectives of young people with neuromuscular diseases regarding their choice of educational programs and possibilities to complete program requirements to gain knowledge for use in future counselling and the development of a national questionnaire survey. The design for this study was qualitative using the interpretive description methodology and Anthony Giddens' theory on modernity and self-identity. Data were generated through two focus group interviews with seven people between 18 and 30 years of age. Beginning and completing an education was influenced by the creation of identity: the importance of experiencing demands and expectations, the meaning of social relations when learning, and the consequences of accessibility for educational opportunities. The participants' sense of self-identity was built by testing boundaries and developing images through social relations with peers, parents, and teachers. How they acted and behaved in the social arena of school and education influenced their choices and chances of completing educational programs.